CUIDANDO DE UM ADOLESCENTE COM TRANSTORNO DEPRESSIVO: UM ESTUDO DE CASO CLÍNICO - Demari, Letícia; Mello, Rosi M. B. d.; Hildebrandt, Leila M.; Piovesan, Solange M. S. (Salão do Conhecimento, 2013)
Resumo